THE RELATIONSHIP BETWEEN WEIGHT GAIN IN PREGNANCY AND PREECLAMPSIA - Hemi Fitriani; Tria Firza Kumala; Nia Rosmiati (Journal of Maternity Care and Reproductive Health, 2019)
Preeclampsia is the second leading cause of maternal death in Indonesia. several risk factors include primigravida, primiparity, hyperplacentosis, family history of preeclampsia/eclampsia, kidney disease, and weight gain. The purpose of this study was to identify the relationship of weight gain during pregnancy with the incidence of preeclampsia in the puerperium of Cimahi City Hospital. This study was conducted using a cross-sectional design. The total sample included 72 pregnant women who selected using purposive sampling techniques. Data collection techniques using observation and interviews. The instruments used were observation sheets and interview sheets. The study was conducted from May to June 2019. Data were analyzed using frequency distribution for univariate analysis and chi-square test for bivariate analysis. This study was approved by the research ethics committee of Sekolah Tinggi Ilmu Kesehatan Jenderal Achmad Yani More than one-third of participants had weight gain more than normal  38.9 % of respondents. There was a significant relationship between weight gain during pregnancy and the incidence of preeclampsia with p-value = 0.033 p-value <α (α = 0.05). The risk of preeclampsia is faced by women who less or more weight gain during pregnancy. It is expected that health workers, especially maternity nurses, would prevent the incidence of preeclampsia by conducting health education and motivation about maintaining weight during pregnancy.Keywords: Weight Gain, Body Mass Index (BMI), Pregnancy, Preeclampsia